Operational Management for “Stockists and Fabrication Abrasion Resistance Plate” in Indonesia - Indra Pamungkas; Rhian Indradewa (Jurnal Syntax Admiration, 2023)
The steel industry between stockists and fabricators is very rare. Business Establishment PT. Gipan Metal Teknik Indonesia (PT.GMTI) combines stockists of abrasion resistant materials and the fabrication process that will be carried out by the company focuses on providing abrasion resistant materials from 4 to 20 thick. The company supports end to end services in the fabrication process which consists of design & drawing process , material, cutting plate, fabrication, forming up to the machining process. The investment value in this company is quite high, so to get a positive profit margin it really depends on operational planning where operational cost calculations are needed to run the company's business. The company makes a profit from the difference between stockist material sales and customization of the fabrication process and production operational costs. The purpose of this research is to determine the importance of operational influence in managing operations to gain company profits. The conclusion of this research is that the operational department needs to implement innovative strategies to be able to compete with competitors in the fabrication industry.